2011
DOI: 10.1002/ase.217
|View full text |Cite
|
Sign up to set email alerts
|

Anatomy as the backbone of an integrated first year medical curriculum: Design and implementation

Abstract: Morehouse School of Medicine chose to restructure its first year medical curriculum in 2005. The anatomy faculty had prior experience in integrating courses, stemming from the successful integration of individual anatomical sciences courses into a single course called Human Morphology. The integration process was expanded to include the other first year basic science courses (Biochemistry, Physiology, and Neurobiology) as we progressed toward an integrated curriculum. A team, consisting of the course directors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 32 publications
0
66
0
2
Order By: Relevance
“…Integrating once separate courses or clinical experiences into a single unit, including combining basic science courses (Schwartz et al 1999;Klement et al 2011), preclinical or clinical preparatory education (Drybye et al 2011), or clinical education (Ogur et al 2007). …”
Section: Practice Pointsmentioning
confidence: 99%
“…Integrating once separate courses or clinical experiences into a single unit, including combining basic science courses (Schwartz et al 1999;Klement et al 2011), preclinical or clinical preparatory education (Drybye et al 2011), or clinical education (Ogur et al 2007). …”
Section: Practice Pointsmentioning
confidence: 99%
“…The young clinical doctors, who undertake intensive work in hospitals, have to continue studies to satisfy the numerous demands in clinical setting. Some reasons account for these problems, such as the medical technology advances, emergence of new diseases, and extension of related medical knowledge (Klement et al, 2011) . However, the effectiveness of the traditional medical teaching system has also been questioned, whether it is adapted well to the current needs of modern medicine, and the current requirements in interdisciplinary pre-clinical and clinical practice (Custers & Cate, 2002) .Traditionally, most of medical educational approaches include didactic lectures given in the classrooms and followed by laboratory or clinical practical days after, where students are expected to verify and master the theoretical knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…As a backbone of medical science, anatomy is generally integrated into the clinical relevant normal human biology. The anatomical curricular changes in the integrated course include placing laboratories and lectures more consistently, decreasing didactic lectures, eliminating unnecessary duplication of content, and increasing students engagement of self-regulated learning time (Hoffmann & Swailes, 2014;Jonassen et al, 2016;Klement et al, 2011) . Integrated medical courses have been gradually accepted by many medical schools, because they appear to improve student learning attitude and satisfaction in comparison with traditional forms of learning.…”
Section: Introductionmentioning
confidence: 99%
“…While the introduction of a new system-based course in anatomy was reported by some authors as having a negative impact on the medical students' knowledge, 20 others have found that an integrated curriculum for the first year of medical school for morphology, biochemistry, physiology, and neurobiology, resulted in higher or equivalent subject examination scores. 21 Our study showed that the implementation of a new curriculum is a difficult task, and that the changes that are being made in education in general and in the teaching of neuroanatomy, in particular, should be critically evaluated and fully debated within the medical community. Although Bologna provided us with some guidelines, how to design the best neuroanatomy course is a question with no standard answer and one that is affected by the resources available in different medical schools.…”
Section: Discussionmentioning
confidence: 92%